Effect of Neem Extract on Fungus Inhibition in Toona ciliata M. Roem. - Thakur, R.; Kumar, R.; Dutt, B.; Sharma, D.; Kumar, G.; Gupta, B.; Heena (International Journal of Economic Plants, 2023)
The increasing human population and continuous demands of timber and its derived products like composite wood, has created a significant pressure on the demand for high quality timber from forests. This, ultimately has resulted in pressurising the natural forests and increase in the unvailibility of the production of high quality or durable timber from the forests. The one way to neutralize this pressure on the forests is to modify the other non durable wood species having undesirable properties like hygroscopicity, anisotropy, dimensional instability and biodegradability. Treatment with neem extracts as a biopreservative proves to be very efficient to protect the wood from bacterial or fungal rots. In the present study, wood specimens of Toona ciliata M. Roem. were treated with neem leaf and seed extracts for 72 hours in concentrations of 0.25, 0.5, 1, 1.5 and 2% (w/v), and analyzed for fungal growth and inhibition on dry weight basis using Polyporous rubidus. The fungal growth was maximum in untreated (control) samples whereas, minimum growth was observed in the neem leaf and seed extracts with 2.00% concentration. This method comes to be one of the most eco-friendly processes of wood preservation and helps in utilization of Toon wood in more effective and sustainable way. Also, the minimal release of harmful chemicals in the environment, helps to widen the industrial applications of Toona ciliata wood and make its acceptance to the society with ease.